PENGARUH KECEPATAN DAN TEGANGAN LISTRIK PENGELASAN "BUTT FLASH", TERHADAP LEBAR HAZ DAN WELD SAMBUNGAN LAS BAJA KARBON RENDAH - - Sutomo (TRAKSI, 2004)
Butt Flash Welding was uged many steel's factory to produce the metal's sheet like coiling sheet steel. In order to speed up the production of coiling sheet steel, two coils sheet steel will be connected each other by this welding. This sheet will be leduced by TCM (Tandem cold Milling). Sometimes this processing has trouble and stopped, because this sheet steel was cutout. This problem Is caused by the wide of HAZ or weld is too large. The smallest of HAZ and weld will use full. In order to this reason research wouldlike to know the effective parameter of velocity and voltage of Butt Flash Welding. The result of this research is vilocity at v = 76/24 mm/sec and voltage at T=7,86 volt will produce a smallest of HAZ & Weld.Key word: Butt flash Welding, velocity, voltage, HAZ and Weld.